Inovasi Disruptif di Industri Perhotelan - Bayudin Bayudin (Universitas Pendidikan Nasional, 2019)
ABSTRACT The concept of a market provider of room rentals or residential units using online networking information technology systems such as those conducted by the Airbnb company is now a new competitive concept in the hotel industry. It is still unclear whether it is considered a threat or not in the development of the hotel industry. The purpose of this study is to analyze the concept of online market place whether it is a disruption to the hotel industry and to analyze the reaction of incumbent companies and government policies in addressing the development of the hotel industry. This research used qualitative method that is constructive with literature review and documentation as the premier data source. The results of the study cover the advantages and disadvantages of the existence of online market places for the hotel industry. This research contributes to the hotel industry that the presence of Airbnb companies as an online market place provider is not a nuisance for incumbent companies in the hotel industry. However, standardization of the quality of rooms or residences that are leased needs to be done to ensure the quality of the products and services offered at online market place. Further studies can be conducted to analyze the application of policies for minimum rental rates for rooms offered both by online market-place provider companies such as Airbnb and incumbent companies in the hotel industry.